Short Communication Effect of Sucrose and Potassi um Metabisulphite on the Physi cochemical and Microbial Analysis of Apricot Pulp (Biological Sciences - PJSIR, 2007)
Effect  of d i fferent  con centrati on s of  su crose  and  potassi um  metabi sul ph i t e  on  th e  apri cot  pu l p  was  studi ed fortnight l y for 90 days throu gh ph ys icoch em ical and m icrobial an a l ysi s. No sign i ficant change i n total sol u bl e sol id s (TSS) of apricot  pu l p was observed d ur i n g the storage. Ac i dity and n on-red uci n g sugar si gn i ficantl y (p